NERACA ENTALPI UNTUK PENENTUAN NILAI KALOR PADA BERBAGAI JINTAN HITAM - Adilah Aliyatulmuna; H.W. Wijaya; M. Murti; M. Rafli (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
The application of the enthalpy balance in solving the calorific value calculation has substituted the application of equation of DU = m(C)(DT). The energy balance refers to (accumulation) = (total energy entering the system) - (total energy leaving the system) + (heat entering the system) - (work done by the system) + (work to enter mass into the system) - (work to remove mass of the system), which produces an enthalpy balance of DH1m1 =DH2m2 generating several assumptions. The assumptions include: first, the system is in a steady state condition; second, the system work (W) is quite small; and third, neglect (Dng)RT results in internal energy (DU) of the nickel wire, having a value almost equal to the enthalpy from the oxidation reaction of the nickel wire. The application of the enthalpy balance requires data on the enthalpy of combustion from a standard material, such as benzoic acid. The result of the enthalpy balance is the positive capacity of the bomb calorimeter. In determining the heat of a material, the enthalpy balance equation requires the value of the calorimeter capacity. This experiment examines the calorific value of black cumin in the form of oil, seeds, and a mixture with 20% coconut oil. The test results indicate that black cumin oil has the highest calorific value, which is in accordance with the referred literature reporting that black cumin oil has a high calorific value, while dried black cumin or seeds and palm oil have a similarly low calorific value.